PERFORMATIVITAS GENDER DAN SEKSUALITAS DALAM WEBLOG LESBIAN DI INDONESIA - Ari Setyorini (Jurnal Kawistara, 2011)
This study is aimed to know how gender and sexuality are performed in weblogs belonging to Indonesian lesbians. This research is particularly purposed to identify the ideological meaning behind the performative identity of lesbian bloggers, and also to measure hir resistance against subordination. This is a multidis-ciplinary-based qualitative research using Foucault’s concepts of power relations and technology of the self (as elaborated in History of Sexuality) and Butler’s theory of performativity. This study then applies Fairclough’s analytical method of Critical Discourse Analysis (CDA). This research takes Fried Durian, an Indonesian lesbian weblog, as its corpus.The result of the research confirms that the identification of lesbian identity tends to be the combination of femininity and masculinity. Through the process of crisscrossing, a lesbian performs hirself by doing “stage performativity”, embedding the identification of feminine and masculine identity through hir appearance, clothing, gesture, and sexuality. Thus, a lesbian blogger is a creative producer in which zie transforms the heteronormative discourse.